Benefits of the ISO 9001 and ISO 14001 standards: A literature review - Juan José Tarí; José Francisco Molina-Azorín; I\~naki Heras (Journal of Industrial Engineering and Management (JIEM), 2012)
Purpose: The purpose of this paper is to determine the similarities and differences between the benefits derived from implementing the ISO 9001 and the ISO 14001 standards. Methodology/Approach: The paper reviews the literature using an electronic search in the ScienceDirect, ABI/Inform, Emerald databases to identify papers focusing on the adoption of the ISO 9001 and 14001 standards and the benefits derived from implementing them. Findings: The paper identifies 82 articles about ISO 9001 and 29 about ISO 14001. Although some differences can be observed between the benefits considered by ISO 9001 and 14001, there is a great degree of coincidence in the benefits studied. The review suggests 13 benefits as the most usually analyzed (including environmental performance for the case of the ISO 14001 standard) by scholars. It is suggested that both standards have clear benefits on operational, people and customer results and that the effects on financial performance are inconclusive. Limitations/implications: One limitation of this paper is that the works identified are conditioned by the search strategy used. In addition, other key words could be included in future studies such as operational, market, quality, financial performance, and customer satisfaction in order to expand this search. Originality/Value: The main contribution is that the paper identifies the literature gap and future research proposals with regard to the benefits of the ISO 9001 and ISO 14001 standards.
Keywords: 650; ISO 9001; ISO 14001; benefits; performance; literature review